2007
DOI: 10.1002/hlca.200790043
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation of Fluorinated 1,3,5‐Triketones

Abstract: The behavior of linear and cyclic fluorinated 1,3,5-triketones and their metal derivatives towards common halogenating agents was examined, and optimal reaction conditions for the straightforward synthesis of mono-, di-, and tetrahalogenated products were found (Schemes 1 -3). An aromatization through a double HBr elimination from an a,a'-dibrominated cyclohexanone was shown to be a promising synthetic route to 1,1'-(2-hydroxy-1,3-phenylene)bis[2,2,2-trifluoroethanones] (= 2,6-bis(trifluoro-A C H T U N G T R E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…19 Triketonate 7 was described in the study. 22 The course of the reactions was monitored by TLC (Silufol UV 254, CHCl 3 as the eluent). The visualization of the spots was performed with the use of aqueous KMnO 4 solutions.…”
Section: Methodsmentioning
confidence: 99%
“…19 Triketonate 7 was described in the study. 22 The course of the reactions was monitored by TLC (Silufol UV 254, CHCl 3 as the eluent). The visualization of the spots was performed with the use of aqueous KMnO 4 solutions.…”
Section: Methodsmentioning
confidence: 99%
“…With these results in hand and using the principles established earlier, 11 we were able to synthesize a range of phenol derivatives 3 with various substituents in the 4position, starting from commercially available cyclohexanones. The corresponding synthetic sequence is depicted in Table 2.…”
mentioning
confidence: 98%
“…10 Indeed, in the course of recent work we observed that the 2,4-dibrominated 1,3,5triketone 4b underwent double dehydrobromination under basic conditions to afford phenol 3b in 31% isolated yield ( Table 1, entry 1). 11 Given the ease of the preparation of both compound 4b and its precursor 2,6-bis(trifluoroacetyl)cyclohexanone (5b, Table 2), 12 we became interested to know whether related reactions could be developed into a general method to synthesize the target 2,6-bis(trifluoroacetyl)phenols 3 ( Table 2). Attempts to directly convert 5b into 3b when conventional oxidants such as elemental sulfur or 2,3-dichloro-5,6-dicyano-1,4benzoquinone were used failed.…”
mentioning
confidence: 99%
See 2 more Smart Citations